Lila Zemborain. El linaje escondido. Rosario, Beatriz Viterbo Editora, 2024, 177 pp. - García, Laura (Badebec, 2025)
Reseña de Lila Zemborain. El linaje escondido. Rosario, Beatriz Viterbo Editora, 2024, 177 pp.